Dualband Microstrip Elliptic Patch 1x4 MIMO Antenna Design for 5G System Device - Rahayu, Yusnita; Andika, Mayo (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2021)
This paper presents a dual-band antenna for the 5G system communication device. The MIMO antenna can potentially boost the capacity and transmission rates to a new level in a communication system. The MIMO 1x4 elliptic circular patch is designed at 24 GHz and 27.8 GHz. From the simulated S11 results, a single patch antenna provides -16.364 dB at 24 GHz and -35.44 dB at 27.86 GHz. While for the MIMO 1x4 patch, the simulated S11 of -15.563 dB and -21.889 dB are achieved at both 24 GHz and 27.8 GHz, respectively. It has a gain value of 9.04 dBi at the 24 GHz and a gain value of 6.56 dBi at the 27.8 GHz. These gains are higher than the gain obtained with a single element.